The Teaching Feedback Process From Comprehensive Pedagogical Strategies - Graciela, Talledo Mendoza Gulissa; Angélica, Atoche-Silva Luz; Tomasita, Herrera Mogollón Rosa; Marleny, Sernaque Barrantes; Monica, Romero Aranda (Migration Letters, 2024)
The research aimed to determine the influence of the comprehensive pedagogical program on the formative feedback of teachers in the Zarumilla district in 2023, using a quasi-experimental design. Pre- and post-tests were applied to an experimental group that received the program and a control group. The sample consisted of 23 teachers (12 in the experimental group and 11 in the control group), selected through non-probabilistic sampling. A 27-item questionnaire was used to collect information, and the Student’s T test was applied to compare means. The results indicated a significant improvement (p<0.05) in the experimental group after the application of the program, supporting the study hypothesis. Furthermore, the influence of the program was observed in the descriptive, discovery and evaluative dimensions.